ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT EKSPOR UMKM EKSPORTIR DI KOTA DENPASAR - Elviony, Jessy; Widanta, Anak Agung Bagus Putu (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2024)
The capital of Bali Province is Denpasar City, which will have 32,226 MSMEs overall by 2022 and many exportable goods on hand. However, Gianyar Regency is the origin of the majority of the handicrafts exported from Bali Province. Additionally, BPS Bali Province noted that in January 2023, Bali's exports decreased by 25.31 percent year over year. Since Denpasar City has a large number of MSMEs with export-worthy products, the goal of this research is to increase the number of exporters in Denpasar City. It is first necessary to understand the factors that can affect interest in exporting in order to increase the number of exporters. This study's theoretical framework is the Theory of Planned Behavior. The structural equation modeling method was the research methodology used in this study. 120 people participated in the study as respondents, and a questionnaire was used to collect their responses. A thorough analysis of all the data gathered revealed that the attitude variable had a favorable and significant impact on export interest, while subjective norms had a favorable but insignificant impact, and behavioral perception control had a favorable and significant impact.